'According to My Righteousness' : Upright behaviour as grounds for deliverance in Psalms 7, 17, 18, 26, and 44, Gert Kwakkel : book review - Branch, Robin Gallaher (Old Testament essays, 2004)
Extracted from text ... Kwakkel, Gert 2002. 'According to My Righteousness': Upright behaviour as grounds for deliverance in Psalms 7, 17, 18, 26, and 44. Leiden/Boston/K?ln: Brill. (Oudtestamentische Studi?n XLVI.) x + 342 pages. Cloth with dust cover. US $116, 00 / _100, 00. ISBN 90-04-125070. In 'According to My Righteousness': Upright behaviour as grounds for deliverance in Psalms 7, 17, 18, 26, and 44, Gert Kwakkel looks at five psalms through the lens of the psalmists' self-evaluations of their upright behaviour (or that of their communities) towards God and man (p 1). In addition to a fine scholarly assessment within this parameter, ..